CiteOpinion: Evidence-based Evaluation Tool for Academic Contributions of Research Papers Based on Citing Sentences - Le Xiaoqiu; Chu Jingdan; Deng Siyi; Jiao Qihang; Pei Jingjing; Zhu Liya; Yao Junliang (Journal of Data and Information Science, 2019)
To uncover the evaluation information on the academic contribution of research papers cited by peers based on the content cited by citing papers, and to provide an evidence-based tool for evaluating the academic value of cited papers.